Narrative Economics : How Stories Go Viral and Drive Major Economic Events - Shiller, Robert J. (Book collections on Project MUSE., 2019)
"Economists have long based their forecasts on financial aggregates such as price-earnings ratios, asset prices, and exchange rate fluctuations, and used them to produce statistically informed speculations about the future--with limited success. Robert Shiller employs such aggregates in his own forecasts, but has famously complemented them with observations about the influence of mass psychology on certain events. This approach has come to be known as behavioral economics. How can economists effectively capture the effects of psychology and its influence on economic events and change? Shiller attempts to help us better understand how psychology affects events by explaining how popular economic stories arise, how they grow viral, and ultimately how they drive economic developments. After defining narrative economics in the book's preface with allusions to the advent of both the Great Depression and to World War II, Shiller presents an example of a recent economic narrative gone viral in the story of Bitcoin. Next, he explains how narrative economics works with reference to how other disciplines incorporate narrative into their analyses and also to how epidemiology explains how disease goes viral. He then presents accounts of recurring economic narratives, including the gold standard, real estate booms, war and depression, and stock market booms and crashes. He ends his book with a blueprint for future research by economists on narrative economics"--